PERKEMBANGAN MASA DEWASA AKHIR (DIATAS 60 TAHUN) KONTEKS AL-QUR'AN DAN HADITS - Muhammad Ardan; Besse Mutmainnah; Indo Santalia; Andi Isni Pujirana (UIN Sumatera Utara Medan, 2025)
Late adulthood is a phase of human development marked by significant physical, cognitive, emotional, and social changes. This paper aims to examine in depth the various aspects that occur in individuals over the age of 60, ranging from body transformation, cognitive decline, to psychosocial challenges faced, such as loneliness, loss of a partner, and adaptation to retirement. The author also discusses the various personality types of the elderly and the factors that influence their character, both in terms of genetics, life experiences, healthc onditions, and social and cultural environments. This paper highlights the importance of an effective communication approach and the crucial role of family and environmental support in maintaining the quality of life of the elderly. With a comprehensive understanding of late adulthood, it is hoped that society can provide proper attention and respect for the elderly and prepare themselves to enter this stage of life more wisely.